Optimal decision-making model for selecting residential green building technologies in China - Lu, Huimin; Juan, Yi-Kai (Frontiers in Environmental Science, 2022)
China is expected to have an annual demand of 1 billion square meters of new residential floor areas in the next few years. Housing developers have adopted various green building technologies (GBTs) in building designs to meet the constantly rising green building (GB) standards. However, they often ignore users’ satisfaction and perception of these GBTs and doubt the cost-benefit assessment of GBTs. This study first constructed GBTs commonly used in residential construction in the Yangtze River Delta region, China. In particular, it adopted the Kano model and the Customer Satisfaction Coefficient (CSC) model to conduct questionnaire surveys on 171 Ningbo households to analyze the differences between developers’ and users’ perceptions of GBTs. Further, a zero-one integer programming (ZOIP) approach was used to build an optimal decision-making model for housing developers to select GBTs that take into account developers’ incremental cost and benefit assessment. The results showed that residents focus on technologies related to comfort and health issues, followed by energy-efficient technologies with lower costs. High-cost and low-scoring GBTs, such as new air systems and Low-E center louvered glass, will be excluded. The decision model clarifies the differences between developers’ and users’ perceptions of GBTs and effectively assists developers in rationalizing the selection of GBTs. Furthermore, it is suggested that the proposed model can be widely applied to other projects in different regions in the future to promote GB markets in China.